2017
DOI: 10.1074/jbc.m117.790170
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical analyses indicate that a bacterial persulfide dioxygenase–rhodanese fusion protein functions in sulfur assimilation

Abstract: Hydrogen sulfide (HS) is a signaling molecule that is toxic at elevated concentrations. In eukaryotes, it is cleared via a mitochondrial sulfide oxidation pathway, which comprises sulfide quinone oxidoreductase, persulfide dioxygenase (PDO), rhodanese, and sulfite oxidase and converts HS to thiosulfate and sulfate. Natural fusions between the non-heme iron containing PDO and rhodanese, a thiol sulfurtransferase, exist in some bacteria. However, little is known about the role of the PDO-rhodanese fusion (PRF) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 51 publications
2
46
0
Order By: Relevance
“…Alternatively, the rhodanese domain can be present in a tandem repeat, as in rhodanese and MST, where the active sites are located in a cleft between the N-and C-terminal domains (14,15). Finally, rhodanese domains are fused to other protein domains as in Cdc25 phosphatase (20) or in the PRF and CstB proteins (23,24).Sulfurtransferases are ubiquitously distributed enzymes that function in a range of pathways including sulfur metabolism, iron-sulfur cluster formation, selenium metabolism, and cyanide detoxification (13,14,(25)(26)(27)(28). In humans, there are five sulfurtransferases including mitochondrial rhodanese and MST, which is found in the cytoplasmic and mitochondrial compartments (29,30).…”
mentioning
confidence: 99%
“…Alternatively, the rhodanese domain can be present in a tandem repeat, as in rhodanese and MST, where the active sites are located in a cleft between the N-and C-terminal domains (14,15). Finally, rhodanese domains are fused to other protein domains as in Cdc25 phosphatase (20) or in the PRF and CstB proteins (23,24).Sulfurtransferases are ubiquitously distributed enzymes that function in a range of pathways including sulfur metabolism, iron-sulfur cluster formation, selenium metabolism, and cyanide detoxification (13,14,(25)(26)(27)(28). In humans, there are five sulfurtransferases including mitochondrial rhodanese and MST, which is found in the cytoplasmic and mitochondrial compartments (29,30).…”
mentioning
confidence: 99%
“…The presence of GHcy-SO 2 H as the only detectable product is consistent with the inability of PDO to process GHcySH through the ultimate hydrolysis step. Crystal structures of PDO homologs indicate that only the sulfur atom of the substrate coordinates to the iron, displacing a single water molecule (16,17). This is similar to isopencillin Nsynthase (22) but contrasts with cysteine dioxygenase, in which the substrate serves as a bidentate ligand donating both the sulfur and the α-amino group (20).…”
Section: Discussionmentioning
confidence: 98%
“…Studies on the Pseudomonas putida PDO and the Burkholderia phytofirmans PRF, a fusion protein containing a PDO domain, have shown that the substrate is within hydrogen bonding distance to the residue corresponding to Arg-163 in human PDO (14,16,17). Arg-163 is involved in hydrogen bonding interactions with Asp-165 and Ser-230 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations